1993
DOI: 10.1002/etc.5620121008
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the anionic surfactant dialkyl sulphosuccinate

Abstract: A range of Organisation for Economic Cooperation and Development (OECD) guideline test systems was used to determine the extent and possible mechanisms of biodegradation of dialkyl sulphosuccinate (DASS, C6/C8). Primary biodegradation of DASS was virtually complete in OECD guideline tests and in simulations of activated sludge sewage treatment systems under both optimal and adverse conditions, and of an anaerobic digester. Ultimate biodegradation increased from about 50% in ready tests to 94% in more powerful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The β-type of sulfosuccinate monoester has previously been obtained by saponification of DOSS; however, this procedure leads to β-EHSS in low purity. 11 To improve on the DOSS based approach, we elected to access [ 13 C] 4 8 In this case, the 13 C NMR signals arising from the 13 Catom enriched sulfosuccinate moiety showed fully resolved multiplets and pairwise mapping of the well differentiated individual 1 J CC scalar coupling constants enabled an unambiguous assignment of C1 and C4 carboxyl atom resonances without recourse to an INADEQUATE experiment ( Figure 2B). As before, an HMBC experiment then served to locate the point of attachment of the ester side-chain to the sulfosuccinate region and in this manner, the compound prepared was confirmed to possess the desired β-type regiochemistry in line with expectation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The β-type of sulfosuccinate monoester has previously been obtained by saponification of DOSS; however, this procedure leads to β-EHSS in low purity. 11 To improve on the DOSS based approach, we elected to access [ 13 C] 4 8 In this case, the 13 C NMR signals arising from the 13 Catom enriched sulfosuccinate moiety showed fully resolved multiplets and pairwise mapping of the well differentiated individual 1 J CC scalar coupling constants enabled an unambiguous assignment of C1 and C4 carboxyl atom resonances without recourse to an INADEQUATE experiment ( Figure 2B). As before, an HMBC experiment then served to locate the point of attachment of the ester side-chain to the sulfosuccinate region and in this manner, the compound prepared was confirmed to possess the desired β-type regiochemistry in line with expectation.…”
Section: Resultsmentioning
confidence: 99%
“…Using model microorganisms, Hales discovered that biodegradative ester hydrolysis of di-n-alkyl sulfosuccinates occurs under aerobic or anerobic conditions to yield both possible monoester regioisomers. 4 More recently, an EPA group established that ethylhexyl sulfosuccinate (EHSS) monoesters are likewise obtained from the branched sulfosuccinate diester DOSS (1) during its biodegradation by oildegrading microorganisms found in the Gulf of Mexico. 5 As part of an ongoing effort to develop a trace analysis for surfactants and their degradation products associated with Corexit oil dispersants in Gulf of Mexico seawater field and laboratory microcosm samples, 6 we required access to stable isotope mass spectrometric standards of α-EHSS (2) and β-EHSS (3) for quantification of LC-MS/MS experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The latter seems less likely, in view of the stability of the C-S bond to hydrolysis (Wagner & Reid, 1931) and the fact that oxidation is required to metabolize primary alkane sulphonates (White & Russell, 1993). Moreover, under anaerobic conditions, dialkylsulphosuccinate undergoes hydrolytic removal of alkyl chains but no desulphonation (Hales, 1993), indicating that the latter is not a hydrolytic process. Thus, oxaloacetate seems to be the most likely identity of the 14C-labelled metabolite, and this proposition is supported by the experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…sewage sludge or river-water) and the assay system (Swisher, 1987;Schoberl e t a/., 1988;Hales, 1993, and references therein). In contrast, ultimate (complete) biodegradation, measured by dissolved-organic-carbon (DOC) removal, CO, production or release of sulphate, was incomplete, varying between 30 % and 70 % depending on the system used (Hales, 1993 ;Swisher, 1987). Hammerton (1 956) showed that biodegradation was influenced by the nature of the alkyl chains and concluded that the ester link was not the point of bacterial attack.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfosuccinate has been identified as an intermediate of bacterial degradation of the anionic surfactant dialkyl sulfosuccinate (DASS) (63). C 6 /C 8 dialkyl sulfosuccinate biodegradation by activated sewage sludge resulted in the formation of sulfosuccinate (30). Moreover, in Comamonas terrigena N3H, sulfosuccinate and octanol were released after the hydrolysis of ester bonds of dioctyl sulfosuccinate (29).…”
Section: Degradation Of Ms Has Been Previously Investigated In Onlymentioning
confidence: 99%